Effect of Dietary Fungus Myceliated Grain on Broiler Performance and Enteric Colonization with Bifidobacteria and Salmonella - Willis, W.L.; Isikhuemhen, O.S.; Ibrahim, S.; King, K.; Minor, R.; Ohimain, E.I. (International Journal of Poultry Science, 2009)
An experiment was conducted to investigate the effects of Fungus (Lentinula edodes) Myceliated Grain (FMG) supplementation on production performance, leukocyte levels and growth of Bifidobacteria and Salmonella populations in broiler chickens. A total of 240 broiler chickens were kept in floor pens and fed a corn and soybean meal based diet with added fungus myceliated grain at 0% (control), 1%, 5% and 10%. The four experimental feeding conditions were replicated six times with ten chicks per replicate. Parameters measured were male and female live body weight, carcass yield, bursa and spleen weights, Salmonella sp. and Bifidobacteria fecal populations and blood differential cell counts. The results from this study revealed no significant differences between treatments in male or female body weight, carcass yield, spleen or bursa weight. Significantly (p